Produção de hidrogênio a partir da reforma de metano e etanol em catalisadores de níquel com suportes a base de CeO2 e CeZrO2 - Dantas, Sandra Cristina (2011)
In the present study, the behavior of nickel catalysts was investigated for the autothermal reforming and steam reforming of methane and ethanol. Nickel samples (15 wt%) supported on Al2O3, CeO2/Al2O3, CeZrO2/Al2O3 and CeZrO2, a sample with ceria addition on Ni/Al2O3 and samples with 5, 10 and 15 wt% nickel supported on CeO2/Al2O3 were analyzed. The catalysts were characterized by BET surface area, X-ray diffraction (XRD), temperatureprogrammed reduction (TPR), CO temperature-programmed desorption (CO-TPD), ethanol temperature-programmed desorption (Ethanol-TPD), X-ray absorption near edge structure spectroscopy (XANES), oxygen storage capacity (OSC) and thermo-gravimetric analysis (TGA). Characterization results showed that for the series of samples with 15 wt% Ni, the ones containing alumina presented higher values of surface area, smaller NiO particle sizes and higher nickel dispersion. TPR, DRS and XANES analysis indicated distinct levels of interaction between nickel and different supports. XANES results indicated the following order of Ni reduction degrees: Ni/CeZrO2 > Ni/CeO2/Al2O3 > Ni/CeZrO2/Al2O3 > Ni/Al2O3. CO-TPD results showed higher redox capacity for the cerium containing samples. Ethanol- TPD presented a more intense hydrogen formation for the catalysts than for the supports, which suggests that the metal promotes the ethanol decomposition reaction. For autothermal reforming of methane, samples supported on alumina presented very similar methane conversions, which can be related with similar values of nickel dispersion. Light-off reaction for steam reforming of ethanol indicated ethylene formation in competition with hydrogen formation for samples supported on alumina. Light-off tests for the autothermal reforming of ethanol reaction showed higher ethanol conversions than the ones obtained during steam reforming in all range of temperature studied. The stability tests during the steam reforming of ethanol indicated that the average size of nickel particles was the propriety that most influenced the activity. In addition, the redox capacity that CeO2 or CeZrO2 supplies to the catalyst was not enough to maintain the catalytic surface free of carbon deposits. The autothermal reforming showed higher ethanol conversions, smaller carbon accumulation and higher hydrogen formation than the ones observed during steam reforming of ethanol. The successive addition of cerium to Ni/Al2O3 catalyst did not result in higher activity, selectivity and stability for autothermal reforming of ethanol reaction. Among samples with different content of nickel, the 10%Ni/12%CeO2/Al2O3 catalyst showed higher ethanol conversion, higher stability, and higher selectivity for hydrogen formation than the others samples. This result can be related to a good balance between active phase and redox capacity, which probably resulted on better performance during autothermal reforming of ethanol.